Pengaruh Corporate Governance Terhadap Kinerja Keuangan Perbankan Pada Bank Konvensional yang Terdaftar di Bursa Efek Indonesia) - Febriyani, Teavionita Sagian; Supriyono, Edy; Sumarta, Nurmadi Harsa (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study was conducted to empirically test how corporate governance affects the financial performance of conventional banking sector companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. Corporate governance variables include institutional ownership, independent committee members, managerial ownership, and frequency of audit committee meetings. As a proxy for bank financial performance, return on equity (ROE) is used. The sample was selected using purposive sampling technique by collecting data from the company's annual report, which resulted in 200 data observations. Panel data regression was used as the research analysis method. The study showed a positive effect of institutional ownership, frequency of audit committee meetings, and managerial ownership on the financial performance of conventional banks. However, a significant influence on the financial performance of conventional banks is not shown by the independent commissioner variable. While control variables such as firm size have a positive influence on the financial performance of conventional banks, the leverage ratio does not significantly affect financial performance. Firm age, on the other hand, shows a negative influence on the financial performance of conventional banks.